EXTERNAL AUDITOR ANALYSIS OF BANKRUPTCY IN ISLAMIC FINANCIAL INSTITUTIONS - Siti Kadariah; Agus; Muslim Marpaung; Emi Masyitah (PT. Radja Intercontinental Publishing, 2023)
Corporate bankruptcy is a process carried out under bankruptcy law, when the company is unable to pay its obligations or reach an agreement with creditors. Creditors can file a lawsuit when the company meets the criteria for bankruptcy. The auditor's opinion consists of five kinds of opinions, namely unqualified (unqualified), unqualified with explanatory language (unqualified with explanatory language), qualified (reasonable), disclaimer (refusal to give an opinion), and adverse (unreasonable). In providing the five opinions above, the auditor must also consider the going concern aspect. Auditors in auditing financial statements are based on auditing standards set by the Indonesian Institute of Accountants which include (1) general standards, (2) fieldwork standards and (3) reporting standards.